IEEE Symposium Conference Record Nuclear Science 2004.
DOI: 10.1109/nssmic.2004.1466833
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lead oxide (PbO) layers for direct conversion X-ray detection

Abstract: Lead oxide (PbO) is a candidate direct conversion material for medical X-ray applications. We produced various samples and detectors with thick PbO layers. X-ray performance data such as dark current, charge generation yield and temporal behavior were evaluated on small samples. The influence of the metal contacts was studied in detail. We also covered large a-Si thin-film transistor (TFT)-plates with PbO. Imaging results from a large detector with an active area of 18 cm 20 cm are presented. The detector has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 14 publications
2
55
1
Order By: Relevance
“…Since the spin-orbit coupling breaks a degeneracy of the 1 u orbitals (see GGA+so in Fig. 2(a)), the selective optical excitation of the electrons localized at E V +1.11 eV can be implemented (α-PbO is known as a good photoconductor [24] for which a mechanism of the optical excitation would be plausible). After selective excitation, the interactions between defects would promote the FM ordering of their localized electrons left at E V +0.60 eV.…”
Section: The Long-range Order Interactionsmentioning
confidence: 99%
“…Since the spin-orbit coupling breaks a degeneracy of the 1 u orbitals (see GGA+so in Fig. 2(a)), the selective optical excitation of the electrons localized at E V +1.11 eV can be implemented (α-PbO is known as a good photoconductor [24] for which a mechanism of the optical excitation would be plausible). After selective excitation, the interactions between defects would promote the FM ordering of their localized electrons left at E V +0.60 eV.…”
Section: The Long-range Order Interactionsmentioning
confidence: 99%
“…The high gain materials under investigation include HgI 2 , PbI 2 , and PbO. [7][8][9][10][11][12] Another approach involves the use of a double layer of a-Se photoconductive material. While a thicker top layer acts as the converter of X rays into electrons and holes, a thinner bottom layer provides further signal amplification by means of an avalanche multiplication mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…, Hunt et al 2007 Another strategy for improving SNR, and thereby DQE performance, of direct detection AMFPIs involves the use of photoconductive materials, such as Pbl 2 , HgI 2 and PbO, which provide significantly higher signal per unit of absorbed x-ray energy than that of the a-Se photoconductors currently used in commercial direct detection devices. (Street et al 2002, Zentai et al 2007, Zuck et al 2003, Hartsough et al 2004, Simon et al 2005 As is the case for a-Se, there is no reported fundamental limitation on the maximum area for any of these photoconductive materials. HgI 2 , in particular, exhibits a number of interesting properties, making it an attractive candidate.…”
Section: Introductionmentioning
confidence: 99%